2012
DOI: 10.5772/52799
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency in Brazilian Refineries under Different DEA Technologies

Abstract: This paper aims to assess the environmental efficiency of refineries in the public sector with emphasis on generated effluents and water consumption in the production process. In order to conduct this research, the addressed method was quantitative with a qualitative approach to the environmental aspects of controllable and uncontrollable variables implemented in two classical models of Data Envelopment Analysis (DEA), considering only desirable outputs and two DEA models which include undesirable outputs. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Moreover, the statistical properties of DEA are established and inference may be performed using bootstrap methods, as discussed in [28]. In recent years, DEA has been widely employed to analyse productivity and technical efficiency, both at an industry level [30][31][32][33][34][35] and in order to compare different countries [21,37]. In the latter case, and after having obtained a measure of the technical efficiency of the various countries, the second step is usually to group them in order to identify some common characteristics related to economic growth.…”
Section: Methodological Approachmentioning
confidence: 99%
“…Moreover, the statistical properties of DEA are established and inference may be performed using bootstrap methods, as discussed in [28]. In recent years, DEA has been widely employed to analyse productivity and technical efficiency, both at an industry level [30][31][32][33][34][35] and in order to compare different countries [21,37]. In the latter case, and after having obtained a measure of the technical efficiency of the various countries, the second step is usually to group them in order to identify some common characteristics related to economic growth.…”
Section: Methodological Approachmentioning
confidence: 99%
“…They found that the production cost was reduced by implementing an environmental management system. Francisco et al (2012) evaluated environmental efficiency. The opinion was that the technological development within oil refineries was largely encouraged by environmental restrictions on the quality of increment in petroleum products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, many studies are based on social issues, focusing on the satisfaction level of employees, customers and, in general, stakeholders [15][16][17][18]; others evaluate company performance on the basis of user-perceived quality, considering this a driver for the company success [19][20]. Studies that analyse the productivity and efficiency of companies are of particular interest [21][22][23], especially those that utilize DEA [24][25][26].…”
Section: Literature Reviewmentioning
confidence: 99%